2016
DOI: 10.1038/srep38874
|View full text |Cite
|
Sign up to set email alerts
|

Placental antibody transfer efficiency and maternal levels: specific for measles, coxsackievirus A16, enterovirus 71, poliomyelitis I-III and HIV-1 antibodies

Abstract: Maternal antibodies transported across the placenta can provide vital immunity against infectious pathogens for infants. We here examine maternal antibody (MA) levels and their association with neonatal antibody levels. Pregnant women of gestational age ≥35 weeks were enrolled at a Guangzhou China hospital and mother-infant paired sera were collected. Measles IgG antibody was detected using ELISA assay, neutralizing antibodies titers against coxsackievirus A16 (CA16), enterovirus 71 (EV71), PV I-III and HIV-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
59
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 29 publications
6
59
1
1
Order By: Relevance
“…The placenta preferentially transfers IgG antibodies (Vidarsson et al, 2014). Although FcRn binds to all IgG subclasses, differences in transfer efficiencies have been noted across the subclasses (IgG1 > 4 > 3 > 2) (Palmeira et al, 2012;Vidarsson et al, 2014;Wilcox et al, 2017) and across IgG1 populations (Fu et al, 2016), raising the possibility for FcRn-mediated preferential selection of IgG1 transfer. Thus, to begin to define the characteristics of antibodies that are preferentially transferred across the placenta, we aimed to define whether the transferred antibodies possessed any qualitative functional differences from those in mothers, focusing on pertussis-specific immunity.…”
Section: Unique Signatures Of Placental Transfer Of Fc Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…The placenta preferentially transfers IgG antibodies (Vidarsson et al, 2014). Although FcRn binds to all IgG subclasses, differences in transfer efficiencies have been noted across the subclasses (IgG1 > 4 > 3 > 2) (Palmeira et al, 2012;Vidarsson et al, 2014;Wilcox et al, 2017) and across IgG1 populations (Fu et al, 2016), raising the possibility for FcRn-mediated preferential selection of IgG1 transfer. Thus, to begin to define the characteristics of antibodies that are preferentially transferred across the placenta, we aimed to define whether the transferred antibodies possessed any qualitative functional differences from those in mothers, focusing on pertussis-specific immunity.…”
Section: Unique Signatures Of Placental Transfer Of Fc Functionmentioning
confidence: 99%
“…Maternal immunization, aimed at enhancing maternal-to-fetal transfer of antibodies, has shown significant promise in boosting newborn immunity (Forsyth et al, 2015), providing a non-invasive strategy to enhance immunity in this vulnerable population. However, epidemiologic studies focusing on matched mother:fetus pairs have found that the extent of immunity transferred varies significantly by antigen (Fu et al, 2016;Palmeira et al, 2012). Specifically, while measles-specific antibodies are transferred efficiently (>100%), antibodies targeting other pathogens, including poliovirus and Coxsackie viruses, are less efficiently transferred (Fu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include the mechanism(s) governing preferential transfer of the IgG1 subclass and the variation of transfer efficiency that can occur based on IgG Fab specificity. Further, whether FcγRs have any role in transplacental IgG transport or whether specific post-translational modifications of IgGs can impact transfer through any mechanism are questions that have not been resolved (9)(10)(11)(12)(13)).…”
Section: Introductionmentioning
confidence: 99%